Analisis Penerapan PSAK 45 (Revisi 2011) Terhadap Penyusunan Laporan Keuangan Entitas Nirlaba (Studi Kasus pada Yayasan Dharma Setia Kosgoro) - ., Hastoni; Pamungkas, Bambang; Mustikawati, Dinah Sobar (Institut Bisnis dan Informatika Kesatuan, 2015)
The financial statement is a very important information to commercial entities and non-profitentities. Due to the existence of the financial statements concerned people can find relevantinformation on the activities undertaken and the progress of the company or organization.Characteristics of non profit entities with different business entities, the main difference lies in theway the fundamental entity obtaining the resources needed to perform various operations activities.The purpose of this study is to analyze the application of PSAK 45 (Revised 2011) in a non profitentity which shaped the foundation. The analysis was performed to obtain data and informationrelating to the above problem. In addition, to determine the extent of compliance or conformity of thefinancial statements presented by the non profit entity of the provisions contained in PernyataanStandar Akuntansi Keuangan (PSAK) Number of 45 Research conducted by the author is in